The theoretical aspects of using customer journey map as a marketing automation toolkit for developing a brand of local treatment facilities made of fiberglass and composite materials - Vira Zhuravel; Andrii Kutsynskyi; Mariia Kutsynska (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The current conditions for the functioning of enterprises-manufacturers of local treatment facilities made of fiberglass and composite materials have been given, a significant impact on the implementation of which is exerted, first of all, by changes in the requirements of consumers of such types of products. The current state of research on the methodological, methodological and theoretical basis for the formation and development of a brand of various products and services with the help of modern marketing tools presented in special and scientific literature has been analyzed, the results of which indicate that attention is paid to these issues and problems. At the same time, regarding methodological approaches to the use of Customer Journey Map as a marketing automation toolkit for brand development, it is advisable to note that such issues are described rather thesis in the recommendations of marketing practitioners, which, in turn, emphasizes the importance of creating a scientifically based basis for practical application in activities of business entities of various forms of ownership under the current conditions of the functioning of the Ukrainian market. The main most commonly used definitions of the concept «brand» have been given. The essence of the Customer Journey Map has been characterized and the sequence of its formation has been summarized. Using the User Scenario and User Story, a portrait of the target group of users of local treatment facilities «specific private households» has been formed. The sequence of using the Customer Journey Map for the purpose of creating (updating, developing) a brand of local treatment facilities made of fiberglass and composite materials has been determined and summarized. Using the built Customer Journey Map for a group of users of local treatment facilities «specific private households», the main steps of such a user and his actions, feelings, thoughts have been identified in order to create (update, develop) a brand of local treatment facilities made of fiberglass and composite materials.